Hydroxyl-substituted double Schiff-base condensed 4-piperidone/cyclohexanones as potential anticancer agents with biological evaluation - Lianshuang Zhang; Qin Chen; Guige Hou; Wei Zhao; Yun Hou (Taylor & Francis Group, 2019)
Novel hydroxyl-substituted double Schiff-base 4-piperidone/cyclohexanone derivatives, 3a-e, 4a-e, 5a-d, and 6a-c, were synthesized and fully characterized by 1H NMR, IR and elemental analysis. The cytotoxicity against human carcinoma cell lines A549, SGC7901, HePG2, HeLa, K562, THP-1 and non-malignant LO2 cell lines were evaluated. The results showed 4-piperidinone derivatives displayed better cytotoxicity than cyclohexanone derivatives, especially for 3,4,5-trihydroxyphenyl-substituted BAP 5c. The western blot and flow cytometry results proved 5c can effectively promote cell apoptosis through up-regulating Bax protein and down-regulating Bcl-2 protein expression. Molecular docking modes showed that 5c could reasonably bind to the active site of Bcl-2 protein through strong intermolecular hydrogen bonds and significant hydrophobic effect. In vivo, 5c can effectively suppress the growth of HepG2 xenografts without apparent body weight changes. This study indicates that 5c can be a potential anticancer agent for early treatment of liver cancers.